TRANSNATIONAL TOURISM DEVELOPMENT: AN EARLY EPISODE FROM COLONIAL SOUTHERN AFRICA - Christian M. ROGERSON (Revista Română de Geografie Politică)
Cross-border tourism marketing and promotion is a widely endorsed approach for encouraging regional tourism development. The aim in this paper is to uncover an early historical example of regional tourism development which occurred in colonial Southern Africa. Using archival sources the study pinpoints the contributions of publicity material produced by South African Railways for the promotion of tourism in the territories of colonial Zimbabwe and Mozambique. In encouraging international tourism to South Africa during the 1920s and 1930s there was an understanding that South Africa’s leading national tourism assets were best packaged together for ‘transnational tourism development’ with marketing for the iconic attraction of Victoria Falls as well as Lourenço Marques. The destination which was promoted as ‘South Africa’ in tourism guidebooks did not correspond with the geopolitical entity of the Union of South Africa, instead it embraced the attractions of Portuguese-controlled Mozambique and several tourism products in the British-controlled territory of Rhodesia.